Computational assessment of the hazardous release dispersion from a diesel pool fire in a complex building’s area - Vasilopoulos, Konstantinos; Mentzos, Michalis; Sarris, Ioannis E.; Tsoutsanis, Panagiotis (MDPI, 2018)
A hazardous release accident taking place within the complex morphology of an urban setting could cause grave damage both to the population’s safety and to the environment. An unpredicted accident constitutes a complicated physical phenomenon with unanticipated outcomes. This is because, in the event of an unforeseen accident, the dispersion of the hazardous materials exhausted in the environment is determined by unstable parameters such as the wind flow and the complex turbulent diffusion around urban blocks of buildings. Our case study focused on a diesel pool fire accident that occured between an array of nine cubical buildings. The accident was studied with a Large eddy Simulation model based on the Fire Dynamics Simulation method. This model was successfully compared against the nine cubes of the Silsoe experiment. The model’s results were used for the determination of the immediately dangerous to life or health smoke zones of the accident. It was found that the urban geometry defined the hazardous gasses dispersion, thus increasing the toxic mass concentration around the buildings.
Keywords: pool fire; urban accident; LES method; FDS model